Identification of immunotherapy and radioimmunotherapy targets on desmoplastic small round cell tumors - Espinosa-Cotton, Madelyn; Guo, Hong-Fen; Tickoo, Satish K.; Cheung, Nai-Kong V. (Frontiers in Oncology, 2023)
Background: Development of successful antibody-based immunotherapeutic and radioimmunotherapeutic strategies rely on the identification of cell surface tumor-associated antigens (TAA) with restricted expression on normal tissues. Desmoplastic small round cell tumor (DSRCT) is a rare and generally neglected malignancy that primarily affects adolescent and young adult males. New therapies capable of treating disseminated disease are needed for DSRCT, which is often widespread at diagnosis. Methods: We used immunohistochemistry (IHC) on fresh frozen surgical specimens and patient-derived xenograft (PDX) tumors and flow cytometry on DSRCT cell lines to evaluate expression of TAAs in these tumors. In vitro cytotoxicity assays were used to evaluate the efficacy of T cell-engaging bispecific antibodies (T-BsAbs) directed at these targets. In vivo, we used an intraperitoneal xenograft mouse model of DSRCT to test T-BsAbs against several TAAs. Results: In DSRCT specimens we found widespread expression of B7-H3, EGFR, GD2, HER2, mesothelin, and polysialic acid, clinical targets for which specific antibody therapeutics are available. The expression of B7-H3, EGFR, HER2, and mesothelin was confirmed on the cell surface of DSRCT cell lines. In vitro cytotoxicity assays confirmed the efficacy of T cell-engaging bispecific antibodies (T-BsAbs) directed at these targets against DSRCT cells. Remarkably, a HER2xCD3 T-BsAb was capable of completely shrinking established tumors in an intraperitoneal mouse model of DSRCT. Conclusions: We propose that these TAAs should be further investigated in preclinical models as targets for immunotherapy and radioimmunotherapy with the hope of providing a rationale to extend these therapies to patients with advanced DSRCT.